Islamic Education in the Perspective of the Qur'an: An Analysis of QS. Al-Rahman Verses 1-4 - M. Miftakhul Huda (Indonesian Journal of Islamic Religion and Culture, 2025)
This study aims to examine the concept of Islamic education contained in QS. Al-Rahman verses 1-4. The research method employed is qualitative research using a literature review approach to analyze interpretations and related literature on these verses. The findings indicate that QS. Al Rahman verses 1-4 emphasize the importance of revelation-based education as the foundation of human life, starting with the teaching of the Qur'an as the primary source of knowledge. These verses also highlight the interconnection between knowledge, moral character, and awareness of Allah's greatness. This study contributes to enriching Islamic education studies by providing a deeper understanding of Qur'an-based education